Superando barreras: aportes para el fortalecimiento del acceso a la justicia de las mujeres en el departamento de Nariño - Barrera Rodríguez, Maria Camila (InSURgência: revista de direitos e movimentos sociais, 2018)
Nariño is a Colombia`s region where there is high indices of violence against women. Although there are different programs and politics to respond this problematic in areas such as health and justice, just 9% of women that attend to institutional offer, have an effective respond to their issues. That`s why, this text in a first moment identify the reasons to women can not access to the justice in Nariño, to give some recommendations to overcome this problematic. Finally, the text proposes strength the System Local Justice that there is in the region of Nariño, through social networks, gender, action without arm and social pedagogic approach. These approaches can articulate the community capacities with institutional offer to provide solutions to women and reduce the gender-based violence in the time.